Longitudinal Study of the Relationship Between Conscious Self-Regulation, School Engagement and Student Academic Achievement - Fomina, T.G.; Filippova, E.V.; Morosanova, V.I. (Psihologičeskaâ nauka i obrazovanie, 2021)
The study seeks to examine the longitudinal relationship between school en¬gagement, conscious self-regulation, and student academic achievement. Research analysis covers the data obtained in two longitudinal studies of two student groups: 8—9 graders (N=106) and 10—11 graders (N=96). Diagnostics of self-regulation was carried out by means of “Self-Regulation Profile of Learn¬ing Activity Questionnaire — SRPLAQ”, school engagement was assessed using “A Multidimensional School Engagement Scale» (Wang et al., 2019; Fomina, Mo¬rosanova, 2020). The average value of annual marks in core academic subjects served as an indicator of academic achievement. The measurements were taken twice, with one-year interval. The study revealed significant changes (decrease) in the level of students’ school engagement during their transition from grade 8 to grade 9. When moving from grade 10 to grade 11, the students significantly increase their levels of self-regulation, school engagement, and academic perfor¬mance. Cross-lagged panel analysis made it possible to establish that conscious self-regulation is a significant predictor of successful learning and high student engagement during the transition to the 9th grade. Whereas in grade 11, student engagement in the educational process, as well as previous academic success, plays a more significant role for successful learning. The data obtained allowed for specifying the directions of the causal relationship between school engage¬ment, conscious self-regulation, and academic achievement of students in differ¬ent periods of schooling. Представлены результаты исследования, направленного на установление характера взаимосвязи между школьной вовлеченностью, осознанной саморегуляцией и академической успеваемостью учащихся. Анализируются данные, полученные в двух лонгитюдных исследованиях, охватыва¬ющих следующие группы респондентов: с 8 по 9 классы (N=106) и c 10 по 11 классы (N=96). Диагностика саморегуляции осуществлялась с помощью опросника В.И. Моросановой «Стиль саморегуляции учебной деятельно¬сти — ССУД-М», школьная вовлеченность оценивалась при помощи ме¬тодики «Многомерная шкала школьной вовлеченности» (Wang et al., 2019, Фомина, Моросанова, 2020). В качестве показателя академической успева¬емости использовался средний балл годовых отметок по основным учеб¬ным предметам. Замеры были произведены дважды с интервалом в один год. Зафиксированы значимые изменения (понижение) в уровне школьной вовлеченности у учащихся при переходе из 8 в 9 класс. У учащихся при переходе из 10 в 11 класс значимо возрастают показатели саморегуляции, вовлеченности и академической успеваемости. Перекрестно-лонгитюдный анализ позволил установить, что осознанная саморегуляция является зна-чимым предиктором успешного обучения и высокой вовлеченности уча¬щихся при переходе в 9 класс. В то же время для успешного обучения в 11 классе более значимую роль играет вовлеченность в учебный процесс, а также предыдущая академическая успешность. Полученные данные по¬зволили установить направления причинно-следственной связи школьной вовлеченности, осознанной саморегуляции и успеваемости школьников в различные периоды обучения.